Eksistensi Madrasah dan Sekolah Islam sebagai Lembaga Pendidikan Islam dalam Sistem Pendidikan Nasional (Studi Kasus di MAN Yogyakarta III dan SMA Muhammadiyah 1 Yogyakarta) - Mukh Nursikin (Postgraduate Program Magister Pendidikan Agama Islam, 2018)
Islamic education has a very important role in the whole of human life. Education is interaction between people, especially between educators and educated in order to achieve the goals of National education. Efforts and intentions of integrating Madrasah and Islamic schools into the real system of National Education and initiatives began to take place during the New Order period. This research method using naturalistic approach. Resources are main people who are determined by snowball and purposive. Data were collected through observation technique, indepth interview, interview/dialogue and documentation. The results of the study described in the SKB Three Ministerial Decrees are